PENGARUH BUDAYA, MOTIVASI KERJA DAN KOMPETENSI TERHADAP KINERJA KARYAWAN - Faizal, Riza; Sulaeman, Maman; Yulizar, Ismayudin (eBA Journal: Journal Economics, Bussines and Accounting, 2019)
The aim of this research is to know and to analyze the influence of work culture, work motivation and competency on employee's performance. The Objects are employees of  BJB bank at Ciamis, Garut and Tasikmalaya). The method used is descriptive. The sample was taken by using total sampling technique with total of the samples 89 people. By path analysis, the research found that work motivation with indicators internal and external motivation; work culture with indicators of Service excellence, Professionalism, Integrity, Respect, Intelligence, Trust included in the high category. Work motivation with indicators of internal motivation and external motivation is included in the sufficient category. Competencies with indicators of Work Quality, Cooperation, Responsibility and Quantity of work are included in the sufficient category. Employee performance with indicators of Work Quality, Discipline Behavior, Use of work time and Attendance are included in the sufficient category. There is a partial positive effect and simultaneous work culture, work motivation and competence on employee performance so that the hypothesis is verified. This means that if the strategy which includes work culture, work motivation and competence is increased, the performance of bank employees to Tasikmalaya, Garut and Ciamis will be better.